A demographic study on vitiligo (sheti) in Bangladesh - Rahman, Mohd. Hafizur; Amin, Md. Ziaul; Rahman, Matiar; Satter, Mohd. Abdus (International Journal of Research in Medical Sciences, 2017)
Vitiligo is quite prevalent and constitutes a major psychological health problem in Bangladesh. To determine the effects and extent distribution of Vitiligo among the people, we mainly focused on the sociodemographic studies on Vitiligo in Bangladesh. The patients volunteered in this study were randomly selected from the Skin and Venereal disease department of Rajshahi Medical college hospital, Rajshahi, Bangladesh during 2009-2011. In this sociodemographic studies 125 vitiligo patients of different age groups were carried out. Age distribution, Sex incidence, occupation, itching, life living status, food allergy, social problem were studied. In this study, disease incidence was the highest 44% among 11-20 years age group. In case of sex incidence the female patients were 56%, on the other hand, male recorded 44%. The demographic characteristic showed that the students were the highest percentage (48%) suffering with Vitiligo by occupation. Family history was the most important survey in this study. 32% patients said they had prior to family history. The maximum patients had living status of middle class (40%). In this study 24% patient complained about Food allergy and the participant patient also complained the social problem of Vitiligo. Eighty percent patients reported that most of the person avoids them because general people know that Vitiligo is an infectious disease. This study will give the social consciousness about Vitiligo i.e. it is not an infectious disease.